Analisis Penggunaan Kata Baku pada Spanduk di Sekolah Kecamatan Pedamaran Kabupaten Ogan Komering Ilir - Rani Syafitri; Ayu Puspita Indah (Universitas Muhammadiyah Surabaya, 2026)
The purpose of this study is to identify and describe errors in the use of standard words on banners in schools in Pedamaran District, Ogan Komering Ilir Regency. The method used is a qualitative method with a descriptive approach. Data were collected through interviews and documentation of banners in schools that were the research samples. The data analysis techniques used by the researcher were data reduction, data collection and drawing conclusions. The results of the study found 8 banners or information boards containing non-standard words from 31 educational units or schools. The number of errors in standard words on these banners or information boards amounted to 18 non-standard words. The results of this study are expected to provide information and awareness to the public about the importance of using standard Indonesian in public communication, as well as being a reference for schools to improve the quality of Indonesian language use in various forms of communication. Keywords: Standard Words, Banners, Information Boards, Schools, Pedamaran.